Differential Impact of Serotonin Transporter Activity on Temperament and Behavior in Persons with a Family History of Alcoholism in the Oklahoma Family Health Patterns Project. (5th May 2014) - Lovallo, William R.; Enoch, Mary‐Anne; Yechiam, Eldad; Glahn, David C.; Acheson, Ashley; Sorocco, Kristen H.; Hodgkinson, Colin A.; Kim, Bojeong; Cohoon, Andrew J.; Vincent, Andrea S.; Goldman, David
<x xml:space="preserve">Abstract</x> Background Central serotonergic (5‐HT) function is implicated in pathways to alcohol dependence, including dysphoria manifested by symptoms of anxiety and depression. However, little is known about genetic variation in central 5‐HT function and its potential impact on temperament and behavior in persons with a family history of alcoholism (FH+). Methods We tested 314 healthy young adults (23.5 years of age, 57% female; 193 FH− and 121 FH+) enrolled in the Oklahoma Family Health Patterns project, a study of alcoholism risk in relation to temperament and behavioral dyscontrol. Dysphoria was assessed using the Eysenck neuroticism and Beck depression scales, and Cloninger's Tridimensional Personality Questionnaire. Risk taking was assessed with the Iowa Gambling Task (IGT) and Balloon Analogue Response Task (BART). All subjects were genotyped for a functional polymorphism (5‐HTTLPR) in the promoter region of the serotonin transporter gene (SLC6A4). Results FH+ subjects with the gain‐of‐function 5‐HTTLPR genotype scored higher in neuroticism, harm avoidance, and symptoms of depression (p‐values ≤ 0.03). No effect of 5‐HTTLPR genotype was seen in FH−. FH+ carriers of the gain‐of‐function 5‐HTTLPR genotype played to minimize their frequency of losses in the IGT, whereas FH− carriers played a balanced strategy (p < 0.003). No 5‐HTTLPR effects were seen in the BART. Results were unaffected by sex, education, drug use, and antisocial characteristics. Conclusions The functional 5‐HTTLPR polymorphism predicted significant variation in negative moods and poorer affect regulation in FH+ persons, with possible consequences for behavior, as seen in a simulated gambling task. This pattern may contribute to a drinking pattern that is compensatory for such affective tendencies.